Design and characterisation of curcumin-loaded nanostructured lipid carriers for safe and efficient topical drug delivery in the treatment of pressure ulcer - Nur Amira Mohd Shamsuddin,; Fazren Azmi,; Khairana Husain,; Leong, Lek Mun; Mohd Hanif Zulfakar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Pressure ulcers (PU) are chronic lesions with a high prevalence in at-risk populations. Although curcumin has various therapeutic properties, its use as a dermal therapeutic agent is limited by its poor solubility and permeability. This study aimed to develop nanostructured lipid carriers (NLCs) to facilitate the topical use of curcumin as wound healing agent in treating PU. The optimised curcumin-NLCs were characterised for their physicochemical properties, drug release, and skin permeation, while effectiveness and toxicity were investigated via cell viability, scratch assays, and an in vivo skin irritation test. The optimised curcumin-NLCs comprised 3.5% solid lipids, 1% surfactant, and 2% co-surfactant with an average particle size of 134.68±6.0 nm, polydispersity index of 0.248±0.00, zeta potential of −44.94±5.44, percentage of encapsulation efficiency of 93.42±0.32%, and drug loading of 0.11±0.00%. CurcuminNLCs showed stable physicochemical properties and extended drug release for up to 48 h, with a cumulative release of 77.72% following a first-order kinetics. The formulation exhibited slower curcumin permeation than the free curcumin. Furthermore, the safe and non-toxic curcumin-NLCs were highly effective at 0.98 µM and showed a high rate of wound closure without skin irritation. Collectively, the NLCs developed for topical delivery of curcumin demonstrated prolonged and sustained release and improved wound healing activity, which indicates that curcuminNLCs are a viable strategy for treating PU.